Building up a network of genetic conservation areas – A comprehensive approach to select target sites for the preservation of genetic variation in wild plant species. (October 2022) - Gradl, Ellen; Lehmair, Theresa A.; Poschlod, Peter; Reisch, Christoph
Abstract: Genetic conservation areas (GCAs) have been proposed as a useful tool to preserve genetic variation of plant populations and communities in situ. Most current strategies to establish GCAs have focused on crop wild relative species and proposals have been made mainly for single species or habitats. Moreover, the analysis of current genetic variation was rarely included as a crucial part in the process of selecting target sites for GCAs. To close this gap, we collected data on the genetic variation in three grassland habitats of three species per grassland type to develop a new approach for the selection of target sites for a network of GCAs. First, we used AFLPs to calculate genetic diversity and genetic differentiation at the target sites. Then we determined how many and which populations represent the highest genetic variation within the study region and should be included in a GCA network. The species differed in the number of populations required and the most suitable target sites were not uniform across species. The species showed different patterns of genetic differentiation among populations. This underlines that the inclusion of further sites is necessary, when aiming at the establishment of GCA networks for multiple species. However, in practical nature conservation genetic variation is not the only relevant parameter for the establishment of a GCA network, we suggest a detailed decision-making process for the establishment of the GCA network, including further important factors such as property situation, funding availability, target species or habitat, land use history or landscape structure.